43rd Biennial Exhibition of Contemporary American Painting. - Cowart, Jack; Damianovic, Maia; Golub, Leon; Kirshner, Judith Russi; Ottmann, Klaus; Pagel, David; Porges, Maria; Price, Marla; Sangster, Gary; Sims, Lowery Stokes; Sultan, Terrie; Tager, Alisa; et al. (Washington : Corcoran Gallery of Art, 1993)
Liu, Hung ; Lutes, Jim ; Marshall, Kerry James ; Miller, Melissa ; Ocampo, Manuel ; Oropallo, Deborah ; Sisto, Elena ; Spero, Nancy ; Applebroog, Ida ; Aptekar, Ken ; Attie, Dotty ; Cruz Azaceta, Luis ; Baechler, Donald ; Davidson, Beattie ; Bramson, Phyllis ; Byron, Michael ; Caroompas, Carole ; Colescott, Robert ; Dingle, Kim ; Frick, Inga ; Garabedian, Charles ; Golub, Leon ; Howe, Catherine ; Humphrey, David
biografie, bibliografie
43rd Biennial Exhibition of Contemporary American Painting, The Corcoran Gallery of Art, Washington, October 30, 1993 - January 2, 1994
Engels
boek